Perlindungan Hukum Debitur Sehubungan Dengan Almasyaqqah Berdasarkan Akad Musyarakah Mutanaqisah (Studi Putusan Pengadilan Agama No. 863/Pdt.G/2020/PA.Mks) - Syakira Almanisa; Richard C. Adam (Dinasti Review Publisher, 2024)
In an agreement, it is crucial for both parties to comprehend the rights and responsibilities that will arise. The agreement also stresses the voluntary responsibility to fulfill obligations, with situations where parties fail to meet their obligations being termed Force Majeure or Masyaqqah events. In the context of Sharia Economic Law, Force Majeure/Masyaqqah refers to circumstances where a party is unable to fulfill their agreed-upon duties due to fatigue, difficulties, and hardships. This concept serves to protect parties experiencing such events. However, in the discussion of Decision Number 863/Pdt.G/2020/PA.Mks, it is explained that parties were unable to meet their obligations due to Force Majeure. This research will also explore the legal protections available to both parties under Sharia Economic Law and applicable Indonesian laws.